Professional Development in Certificate Educational Studies Leadership (CESL) for School Literacy Movement - Latifah, Nur; Ms, Zulela; Agustiningsih, Walisa Tri (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2020)
The purpose of this research is to analyze the improvement of the professional competencies of teachers who participated in the